Imaging Findings of COVID-19 on Computed Tomography: A Narrative Review - Almeida, Rui Pedro (2023)
Introduction: In December 2019, in the Chinese city of Wuhan, a respiratory infection caused by the SARS-CoV-2 virus was identified for the first time in humans. The disease caused by this virus continues to spread around the world, representing a major global health problem. Considering that computed tomography (CT) of the chest is an essential exam to evaluate and determine the extent of lung lesions that may occur, this review aims to describe the most characteristic and common imaging findings caused by Covid-19. Materials and Methods: In this narrative review, articles from the ScienceDirect scientific platform were analyzed, using the following research equation: “Covid-19 AND ("radiological findings" OR "image findings") AND radiography and CT”. Articles published in English, in the timeframe from 2020 to 2023, and using filtering to select open access articles on the Eduroam network, corresponding to the typology of research or review articles, were considered. In total, 10 articles were considered for narrative analysis according to the SANRA scale (Scale for the Assessment of Narrative Review Articles), selected based on the PRISMA checklist (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Results: The consulted literature reports that the most frequent CT imaging findings are ground-glass opacity, lung consolidations, mosaic paving, lung fibrosis and vascular thickening, with the lungs being more affected peripherally and in the lower lobe region Conclusion: The imaging patterns of Covid-19 on chest CT usually follow typical characteristics, although they are not pathognomonic as they lack specificity in differentiating the radiological semiology of different types of pneumonia. However, CT remains useful in determining the location and extent of lesions caused by this virus.